Galectin-3 drives oligodendrocyte differentiation to control myelin integrity and function - Pasquini, L.A. (2011)
Galectins control critical pathophysiological processes, including the progression and resolution of central nervous system (CNS) inflammation. In spite of considerable progress in dissecting their role within lymphoid organs, their functions within the inflamed CNS remain elusive. Here, we investigated the role of galectin-glycan interactions in the control of oligodendrocyte (OLG) differentiation, myelin integrity and function. Both galectin-1 and-3 were abundant in astrocytes and microglia. Although galectin-1 was abundant in immature but not in differentiated OLGs, galectin-3 was upregulated during OLG differentiation. Biochemical analysis revealed increased activity of metalloproteinases responsible for cleaving galectin-3 during OLG differentiation and modulating its biological activity. Exposure to galectin-3 promoted OLG differentiation in a dose-and carbohydrate-dependent fashion consistent with the glycosylation signature of immature versus differentiated OLG. Accordingly, conditioned media from galectin-3-expressing, but not galectin-3-deficient (Lgals3/) microglia, successfully promoted OLG differentiation. Supporting these findings, morphometric analysis showed a significant decrease in the frequency of myelinated axons, myelin turns (lamellae) and g-ratio in the corpus callosum and striatum of Lgals3/compared with wild-type (WT) mice. Moreover, the myelin structure was loosely wrapped around the axons and less smooth in Lgals3/mice versus WT mice. Behavior analysis revealed decreased anxiety in Lgals3/mice similar to that observed during early demyelination induced by cuprizone intoxication. Finally, commitment toward the oligodendroglial fate was favored in neurospheres isolated from WT but not Lgals3/mice. Hence, glial-derived galectin-3, but not galectin-1, promotes OLG differentiation, thus contributing to myelin integrity and function with critical implications in the recovery of inflammatory demyelinating disorders. © 2011 Macmillan Publishers Limited All rights reserved.